Arctic Tundra Land Cover Classification on the Beaufort Coast Using the Kennaugh Element Framework on Dual-Polarimetric TerraSAR-X Imagery - Willeke A’Campo (Department of Physical Geography, Stockholm University); Annett Bartsch (b.geos); Achim Roth (German Remote Sensing Data Center (DFD), German Aerospace Center (DLR)); Anna Wendleder (German Remote Sensing Data Center (DFD), German Aerospace Center (DLR)); Victoria S. Martin (Centre for Microbiology and Environmental Systems Science, University of Vienna); Luca Durstewitz (Department of Physical Geography, Stockholm University); Rachele Lodi (Institute of Polar Science (ISP-CNR), National Research Council, Italy); Julia Wagner (Department of Physical Geography, Stockholm University); Gustaf Hugelius (Department of Physical Geography, Stockholm University) (Remote Sensing, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1597265 The abstract is available here: https://uscholar.univie.ac.at/o:1597265